2006
DOI: 10.1007/s00428-006-0183-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of dysadherin and E-cadherin in lymph node metastases of colorectal carcinoma

Abstract: Reduction/loss of E-cadherin is associated with the development and progression of many epithelial tumors, while in a limited number of neoplasms, E-cadherin is re-expressed in metastases. Dysadherin, recently characterized by members of our research team, has an anti-cell-cell adhesion function and downregulates E-cadherin in a posttranscriptional manner. Colorectal cancer (CRC) is one of the most common tumors in the developed world, and lymph node metastases are harbingers of aggressive behavior. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 37 publications
2
24
0
2
Order By: Relevance
“…LEPR was associated with pituitary adenoma, 12,20,46 FXYD5 was associated with a broad spectrum of cancers, and KCNMA1 was also associated with giloma. 3,19,27,41 The number of overlapping genes between each pair of the 3 data sets was higher: 26 between the UCLA and USC studies, 34 between the Scheck and USC studies, and 35 between the UCLA and Scheck studies. Interestingly, we found that the MN1 gene was also differentially expressed in the UCLA data set.…”
Section: Gene Expression Analysismentioning
confidence: 96%
“…LEPR was associated with pituitary adenoma, 12,20,46 FXYD5 was associated with a broad spectrum of cancers, and KCNMA1 was also associated with giloma. 3,19,27,41 The number of overlapping genes between each pair of the 3 data sets was higher: 26 between the UCLA and USC studies, 34 between the Scheck and USC studies, and 35 between the UCLA and Scheck studies. Interestingly, we found that the MN1 gene was also differentially expressed in the UCLA data set.…”
Section: Gene Expression Analysismentioning
confidence: 96%
“…It is estimated that dysadherin expression would be a good biological predictor for cell invasion and metastasis in human cancers (Hirohashi and Kanai 2003;Shimamura et al 2004). It was reported that dysadherin expression has prognostic importance in advanced colorectal cancers (Batistatou et al 2006). Dysadherin is also known as Fxyd domain containing ion transport regulator 5 (FXYD5).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] While the role of dysadherin in gastric cancer has been studied in detail, in oesophageal cancer its role remains mainly unexplored. 7,9,10 In a clinical study from Shimada et at 11 expression of dysadherin was studied in 117 patients with oesophageal squamous cell carcinoma of all stages.…”
mentioning
confidence: 99%
“…In accordance to what has been shown in relevant studies exploring the role of dysadherin in extraoesophageal human cancers, multivariate analysis revealed that in squamous cell carcinomas of the oesophagus, although expression of E-cadherin is not an independent prognostic factor, expression of dysadherin is (p<0.05). 6,11 At present and in contrary to E-cadherin, there is no research investigating the association of dysadherin with oesophageal adenocarcinoma. 12 This is particularly important in the West, where adenocarcinoma subtype comprises more than 80% of oesophageal cancers.…”
mentioning
confidence: 99%